The Expectation Value of Electron Momentum of Li2+ ion on Principal Quantum Number n ≤ 3 in Momentum Space - Amar Ma'ruf Al Bawani; Bambang Supriadi; Muhammad Ivan Syahdilla; Nafiista Barkania Ayu Benani; Chintya Rahmawati Zuhri (UNIVERISTAS PGRI MADIUN, 2023)
Information on electron behavior in a hydrogen atom, such as electron expectation, electron probability, electron position, electron energy spectrum, etc. can be obtained through Schrodinger equation.ions are atoms that lose so that they become hydrogenic atoms. This research aims to determine the expectation value of electron momentum of ion in momentum space at the main quantum number using Schrodinger equation approach. The method used in this research is literature study with non-experimental research type. The results obtained expectation value depends on the interval and the value of the quantum number. The larger the interval, the expectation value of electron momentum increases. While the greater the value of quantum numbers, the expectation value of electron momentum is getting smaller. Based on the analysis, the expectation value of electron momentum is quite varied from to . From this research, it is found that the expectation value of electron momentum is the same as the expectation value of electron position.